Geotechnologies to estimate flooded rice crop area - Marcos Adami; Mauricio Alves Moreira; Bernardo Friedrich Theodor Rudorff; Rodrigo Rizzi; Brummer Seda Alvarenga; Enzo D’Arco (Revista Brasileira de Cartografia, 2006)
The estimate of the main crops is fundamental to plan the agricultural sector and for the generation of statistics on the future crops. Among several products of importance in the national agricultural scenery, the rice crop represents an important participation of the total Brazilian grain production. Most of this production is found in the Southern States of the country, mainly in Rio Grande do Sul state, standing for about 47% of the national production. Several producing areas in this state showed a big expansion of this crop in its extreme southern region, not only in the technological development but also in the development of new varieties. The objective of this work was to calculate the area cultivated with flooded rice in the county of Santa Vitória of Palmar, Rio Grande do Sul State, using TM and ETM+ sensors images from the satellites Landsat 5 and 7, respectively. The images were acquired along the crop season in order to define the most favorable period for their acquisition. The multitemporal analysis of the images allowed estimating the flooded rice area in 60.557 ha, underestimating in 1,67% the official data from the IRGA (Rice Institute of Rio Grande do Sul). When analyzed the dates individually the March image showed an excellent result. In the multitemporal analysis, the classifications using the months of November + December and only December obtained satisfactory results and with the advantage to supply a forecast planted area with flooded rice.